Sequential Extraction Study of Stability of Adsorbed Mercury in Chemically Modified Activated Carbons - Tong, Shitang; Fan, Mingxia; Mao, Lei; Jia, Charles Q (Environmental science & technology, 2011)
Activated carbons chemically modified with sulfur and bromine are known for their greater effectiveness in capturing vapor Hg from coal combustion and other industrial flue gases. The stability of captured Hg in spent activated carbons determines the final fate of Hg and is critical to devising Hg control strategy. However, it remains a subject that is largely unknown, particularly for Br-treated activated carbons. Using a six-step sequential extraction procedure, this work evaluated the leaching potential of Hg captured with four activated carbons, one lignite-derived activated carbon, and three chemically treated with Br2, KClO3, and SO2. The results demonstrated clearly the positive effect of Br- and SO2-treatment on the stability of captured Hg. The Hg captured with brominated activated carbon was very stable and likely in the form of mercurous bromide complex. Sulfur added at high temperature with SO2 was able to stabilize a majority of Hg by forming sulfide and possibly sulfonate chelate. The presence of sulfate however made a small fraction of captured Hg (<10%) labile under mild conditions. Treating activated carbon with KClO3 lowered the overall stability of captured Hg. A positive dependence of Hg stability on Hg loading temperature was observed for the first time.